Fourier-Stokes polarimetry of fields corresponding to linearly and circularly polarized birefringent protein networks - Karachevtsev, A.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Considered in this work are the possibilities to use the method of FourierStokes polarimetry for diagnostics of optical anisotropy inherent to polycrystalline networks of biological layers. The authors have offered a generalized model for optical anisotropy of histological sections taken from biological tissues and films of biological liquids. Polarization maps for Fourier spectra of laser images describing the phaseinhomogeneous objects have been investigated. Grounded was application of the method for consistent spatial-frequency filtration of polarization maps formed by linear and circular birefringent of biological crystals.